2016
DOI: 10.1002/per.2081
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Adjustment and Social Justice Behaviour: The Role of Individual Differences in Multicultural Personality

Abstract: Note: α Description ratings based on reliability matrix in Ponterotto and Ruckdeschel (2007).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 60 publications
2
25
2
2
Order By: Relevance
“…An update by Ratts, Singh, Nassar-McMillan, Butler, and McCullough (2016), which occurred during the data collection of this study, wedded the MCCs to a social justice framework, rebranding them as the Multicultural and Social Justice Counseling Competencies. The addition of a social justice component to the MCC framework is critical to implementing action among counselors to improve society for all members, and the evidence from this study and Fietzer et al (2016) suggests that the Social Justice and Activism subscale of the MPI may be an effective predictor of such behavior.…”
Section: Limitations and Future Researchmentioning
confidence: 89%
See 3 more Smart Citations
“…An update by Ratts, Singh, Nassar-McMillan, Butler, and McCullough (2016), which occurred during the data collection of this study, wedded the MCCs to a social justice framework, rebranding them as the Multicultural and Social Justice Counseling Competencies. The addition of a social justice component to the MCC framework is critical to implementing action among counselors to improve society for all members, and the evidence from this study and Fietzer et al (2016) suggests that the Social Justice and Activism subscale of the MPI may be an effective predictor of such behavior.…”
Section: Limitations and Future Researchmentioning
confidence: 89%
“…During initial validation, the MPI demonstrated (a) sufficient evidence of factor structure with exploratory and confirmatory analyses on independent samples; (b) no contamination with social desirability; and (c) evidence of convergent validity with measures of multicultural scales predicted to be related proximally, medially, and distally with the MPI (Ponterotto et al, ). Lastly, the MPI demonstrated predictive validity (Fietzer et al, ) with social justice behavior and incremental validity above broad measures of personality. The MPI‐SF demonstrated confirmatory evidence of factor structure, incremental validity beyond broad traits of personality, and predictive validity with measures of collegiate adjustment in an independent sample of 333 college students (Fietzer et al, ).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Despite the pedagogical and training advantages assessment of the FFM would offer for improving social justice engagement, we are aware of one study that examined personality traits and their influence on social justice. Fietzer et al (2016) examined whether broad personality traits affected social justice behavior as modeled by a behavioral economics paradigm and self‐reported social justice attitudes among a sample of 153 undergraduates. Although Fietzer et al (2016) found no relationship between personality traits and social justice behavior as measured by the behavioral economics paradigm, self‐reported social justice attitudes correlated with extraversion and openness.…”
Section: Demographics Personality and Context As Predictors Of Socimentioning
confidence: 99%